KHAN AND THE PERSONALITY IN THE INDIAN MOVIE MY NAME IS KHAN - Yasin Azhari (Asosiasi Dosen Muda Indonesia, 2024)
This research is aimed to know the character of Khan, a main character in the My Name is Khan Movie, and to know Khan’s as an Asperger sufferer and now his personality influenced him in a relationship. The research was conducted by analyzing evidence from the dialogue and Khan’s actions in the Movie. The writer used the descriptive-qualitative method in this paper. The writer employs himself to collect the data by reading the script, watching the Movie, and marking it. The objectives of the study are to understand and to describe the characteristics of Khan’s character in relationship. The result shows that the main character of Khan as an Asperger sufferer is depicted psychologically. He is a loving man, honest, and tolerant, Khan is a simple Muslim who helps anyone without looking at the race, religion, and ethnicity of people whom he helps. He never shows any hatred toward the non-Muslim community. He believes that real brotherhood will only be possible to be implemented if people respect each other. Furthermore, has been a very good man with extraordinary characteristics, Khan is also able to do an impossible and extraordinary journey to meet the president of the USA to tell that he is a Muslim and he is not a terrorist and thus keeps his promise to his wife.